Sistem Webgis Dan Multi Sensor Untuk Pemantauan Debit Dan Volume Air Berbasis Realtime Operating System - Fathul Razak (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Real Time Operating System (RTOS) is an operating system that runs multitasking processes on Embedded systems and non-RTOS is a system that runs its work sequentially and then loops, because of that data reading becomes slower. In this study, an experiment was conducted to read the discharge and volume of water using RTOS and non-RTOS systems, the results of which will be displayed on WebGIS. It is known that the RTOS system is faster in reading data than non-RTOS systems, this is because the RTOS system runs the scheduled task process for a certain time, therefore the time required to read data on the device becomes faster compared to non-RTOS systems. This study also uses the standard deviation statistical method, which calculates the accurate level of reading of discharge data and water volume when passing through the sensor and storing data, the smaller the standard deviation value, the more accurate the data will be. After 10 experiments using 3 liters of water, the RTOS results are 1 second faster than non-RTOS in reading the discharge data and water volume. Then the standard deviation value on RTOS is smaller than non RTOS.